Optical Taxonomic Signal and the Diagnosis of Alzheimer's Disease - Frank A. Greco; Brent R. Schell; Eugene B. Hanlon (IEEE Open Journal of Engineering in Medicine and Biology)
Goal: We previously demonstrated that near-infrared spectroscopy in vivo presents spectral features at 895 and 861 nm that accurately classify Alzheimer's disease, mild cognitive impairment, and age-matched control subjects. Our purpose here is to associate the 895 nm signal with $β$ -amyloid. Methods: We applied our feature selection technique to subjects with and without leptomeningeal amyloid. We developed a novel concept, optical taxonomic signal, to determine the dependence of signal on source-detector distance. Results: Features at 891 and 768 nm discriminate between subjects with and without leptomeningeal $β$ -amyloid. The variation of optical taxonomic signal with source-detector distance indicates that both signals come from the leptomeninges and not cerebral cortex. The two features are highly correlated and likely result from the same cellular material. Conclusions: The discovery of an 891 nm feature that clearly depends upon the presence of $β$ -amyloid supports our hypothesis that the 895 nm feature previously discovered also reports $β$ -amyloid.